Critical Item Analysis Enhances the Classification Accuracy of the Logical Memory Recognition Trial as a Performance Validity Indicator. Issue 5 (4th July 2021) - Dunn, Alexa; Pyne, Sadie; Tyson, Brad; Roth, Robert; Shahein, Ayman; Erdodi, Laszlo
ABSTRACT: Objective: : Replicate previous research on Logical Memory Recognition (LM Recog ) and perform a critical item analysis. Method: : Performance validity was psychometrically operationalized in a mixed clinical sample of 213 adults. Classification of the LM Recog and nine critical items (CR-9) was computed. Results: : LM Recog ≤20 produced a good combination of sensitivity (.30-.35) and specificity (.89-.90). CR-9 ≥5 and ≥6 had comparable classification accuracy. CR-9 ≥5 increased sensitivity by 4% over LM Recog ≤20; CR-9 ≥6 increased specificity by 6–8% over LM Recog ≤20; CR-9 ≥7 increased specificity by 8–15%. Conclusions: : Critical item analysis enhances the classification accuracy of the optimal LM Recog cutoff (≤20).